From Montaigne to Montaigne - Levi-Strauss, Claude (Book collections on Project MUSE., 2019)
"This slim volume, published in the same series as Foucault's Language, Madness, and Desire. It brings together two lectures that Levi-Strauss gave on the French essayist Montaigne: one given in 1937 and the second in 1992"--